AI is here to stay - Jazbec, Saša (ELOPE (Ljubljana), 2025)
Artificial intelligence (AI) is a disruptor increasingly impacting foreign language learning and teaching. This paper explores the theoretical framework of AI, its application in foreign language teaching, and the question of whether AI is displacing foreign language teachers. The empirical part presents findings from a survey of English and German teachers (n = 112) in Slovenian primary and secondary schools regarding their views on AI in foreign language teaching. Statistical analysis reveals a constructively critical attitude towards AI among teachers, acknowledging its presence in and influence on teaching strategies, methods, and teacher roles but not perceiving it as a fundamental threat. Furthermore, statistical tests and correlations indicate no significant differences in attitude towards AI in the classroom based on whether they are English or German teachers or whether they work in primary or secondary schools.
Keywords: angleščina kot tuji jezik; artificial inteligence; English as a foreign language; German as a foreign language; nemščina kot tuji jezik; pouk tujega jezika; teaching a foreign language; umetna inteligenca